Cardiometabolic risk profile and associated factors among adults with type 2 diabetes in a primary health care clinics in North Central Nigeria - Innocent N. Okonkwo; Maryanna Idoh; Ezra O. Agbo; Edwin N. Okafor (African Journal of Primary Health Care & Family Medicine, 2026)
Background: Cardiometabolic abnormalities substantially increase morbidity among individuals with type 2 diabetes mellitus (T2DM), particularly in primary health care (PHC) settings. In Nigeria, evidence on comprehensive metabolic risk profiling beyond glycaemic control remains limited. Aim: To determine the cardiometabolic risk profile and identify factors associated with adverse cardiometabolic outcomes among adults with T2DM. Setting: The study took place at government-owned PHC facilities in Makurdi, Benue State, Nigeria. Methods: This facility-based analytical cross-sectional study systematically recruited 120 eligible adults aged ≥ 30 years with T2DM. Socio-demographic and clinical data were obtained using structured questionnaires and medical records. Laboratory analyses assessed glycaemic status, lipid profile and renal function. Renal impairment was determined using estimated glomerular filtration rate (eGFR) based on standard clinical thresholds. Cardiometabolic abnormality was defined as the presence of at least one abnormal component: poor glycaemic control, dyslipidaemia or renal impairment. Data were analysed using descriptive statistics and logistic regression. Results: The mean age was 56 ± 10.8 years, with females comprising 61.7%. The mean diabetes duration was 4 ± 3.2 years. Overall, 84.8% had at least one cardiometabolic abnormality. Poor glycaemic control, dyslipidaemia and renal impairment occurred in 65.8%, 65.0% and 29.2%, respectively. The mean cardiometabolic risk score was 1.87 ± 1.05. Longer diabetes duration independently predicted poor glycaemic control (p < 0.05). Conclusion: Adults with T2DM attending PHC clinic had a high burden of cardiometabolic abnormalities, highlighting the need for integrated diabetes management strategies. Contribution: The study provides context-specific evidence to support routine lipid and renal function assessment in resource-limited settings.